2021
DOI: 10.3390/diagnostics11050786
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 18F-PBR-111 in the Cuprizone Mouse Model of Multiple Sclerosis

Abstract: The study aims to assess site assessment of the performance of 18F-PBR-111 as a neuroinflammation marker in the cuprizone mouse model of multiple sclerosis (MS). 18F-PBR-111 PET imaging has not been well evaluated in multiple sclerosis applications both in preclinical and clinical research. This study will help establish the potential utility of 18F-PBR-111 PET in preclinical MS research and future animal and future human applications.18F-PBR-111 PET/CT was conducted at 3.5 weeks (n = 7) and 5.0 weeks (n = 7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Lastly, the work by Jewells et al utilizes novel in vivo detection of microglia through PET detection of 18-kDa translocator protein (TSPO) radiotracer in demyelinating mice model of MS [ 13 ]. TSPO, also called the peripheral benzodiazepine receptor (PBR), is highly expressed in activated microglia and a known prognostic factor in MS pathology.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the work by Jewells et al utilizes novel in vivo detection of microglia through PET detection of 18-kDa translocator protein (TSPO) radiotracer in demyelinating mice model of MS [ 13 ]. TSPO, also called the peripheral benzodiazepine receptor (PBR), is highly expressed in activated microglia and a known prognostic factor in MS pathology.…”
mentioning
confidence: 99%
“…TSPO, also called the peripheral benzodiazepine receptor (PBR), is highly expressed in activated microglia and a known prognostic factor in MS pathology. For this purpose, the Authors develop a specific 18F-PBR-111 radiotracer and demonstrated significant uptake after demyelination that was spatially correlated with positive histopathological staining of CD11b (activated microglia) and F4/80 (macrophages) [ 13 ]. This increase in uptake was greater when compared to control mice and located in the corpus callosum and striatum [ 13 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation